Correlation Between Reading and Writing on First Semester Students at Informatics Program University of Bina Insan - Herlina herlina; Melati Melati; Lisa Rakhmanina (Edu-Ling: Journal of English Education and Linguistics, 2021)
The objective of this study is to find out whether or not there is any significant correlation between reading and writing skills at Informatics Program University of Bina Insan in Academic Year of 2020/2021. The problem is there any significant correlation between students’ reading skill and their writing skill at Informatics Program University of Bina Insan in Academic Year of 2020/2021?. There were two hypotheses in this study, null hypothesis (Ho) is stated that there is no significant correlation between the first students’ reading skill and writing skill at Informatics Program University of Bina Insan the Academic Year of 2020/2021 (robtained<rtable) and alternative hypothesis (Ha) is states that there’s significant correlation between the first students’ reading and writing skills at Informatics Program University of Bina insan Academic Year of 2020/2021 (robtained<rtable). In this study, descriptive correlation method was used. The population of this study was the first students at Informatics Program University of Bina Insan Academic Year of 2020/2021. The sample of this study was all class which consisted of 34 students. The sampling technique used in this study was total sampling. In order to collect the data, the documentation was used. To analyze the data, the Pearson Product Moment formula was applied. The result of this research was 0.473. While, critical value of rtable was 0.349 at the level of significant 0.05 or 95% in two tailed test. It indicated that there was moderate correlation. The null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that there was moderate correlation between students’ reading and writing skills at Informatics Program University of Bina in Academic Year of 2020/2021.